Grid batch-dependent tuning of glow discharge parameters - Kazan, Ramy; Bourgeois, Gabrielle; Carisetti, Dominique; Florea, Ileana; Larquet, Eric; Maurice, Jean-Luc; Mechulam, Yves; Ozanam, François; Schmitt, Emmanuelle; Coureux, Pierre-Damien (Frontiers in Molecular Biosciences, 2022)
Sample preparation on cryo-EM grids can give various results, from very thin ice and homogeneous particle distribution (ideal case) to unwanted behavior such as particles around the “holes” or complexes that do not entirely correspond to the one in solution (real life). We recently run into such a case and finally found out that variations in the 3D reconstructions were systematically correlated with the grid batches that were used. We report the use of several techniques to investigate the grids’ characteristics, namely TEM, SEM, Auger spectroscopy and Infrared Interferometry. This allowed us to diagnose the origin of grid preparation problems and to adjust glow discharge parameters. The methods used for each approach are described and the results obtained on a common specific case are reported.